Ouvidos de Mercado: novas configurações da comunicação e de consumo digital na cena paulistana - Bento, Igor da Costa (2010)
The process of symbiosis between information networks and the urban areas gives rise to an informational dimension of ubiquitous access to cyberspace that promotes the emergence of a myriad of new social practices from the appropriation of these networks and a variety of connection devices (cell phones, palms, MP3 players, etc.). Nomadic listening is one of the social practices identified in the current urban scene. It can be seen as a semiotic modulation, also social, cognitive, corporal and it works on the coupling between mobile devices and the act of roaming through the city. This new form of consumption focuses on listening to digital music and mounting customized playlists as soundtracks for the day to day. From a conceptual framework that focuses on the intersection between media and consumption, this paper aims to map the nomadic listening in the urban scene and to understand how the music industry has incorporated this practice into their promotion and commercialization strategies.